Un modelo cualitativo para el análisis estratégico de organizaciones : Aplicación y propuestas de alternativas en un estudio de caso - Ferro Moreno, Santiago (2015)
The strategic analysis of organizations is based on the internal and external environments, in order to identify positive and negative variables and factors. The interrelation and timing of these strategic forces are essential to create alternative solutions that tend to achieve the organizational objectives.The normative prospective has theorical and methodological foundations to create a desired future and from it, be able to identify impelling and restraining forces that have influence on the particular problematic situation (go from the current situation to a better one in a certain time).The aim of this article is to analyze on a strategic way a real case with a normative-prospective model that considers the temporal dynamics of the factors impact and variables in time allowing to suggest alternative solutions.Semi-structured interviews were performed with all the employees of this case and structured observations and workshops with the commercial and general management.In consequence, with the results, the desired, current and improved situations were built. Additionally, forces were identified classified and appreciated and lastly solutions were suggested. With the proposed prospective method, alternative solutions could be constructed in order to settle temporary organizational objectives. No constraints were found to use the current method in other cases.